Assessing textbook outcomes following major liver surgery in association with obesity at a referral academic center - Khajeh, Elias; Fakour, Sanam; Ünal, Umut Kaan; Sabetkish, Nastaran; Leins, Johannes; Ramouz, Ali; Mieth, Markus; Sabagh, Mohammad Sadegh; Abbasi Dezfouli, Sepehr; Golriz, Mohammad; Büchler, Markus W.; Mehrabi, Arianeb (European journal of surgical oncology, 2023)
Introduction - Outcomes of major surgeries in tertiary educational hospitals have been complicated by the referral of high-risk patients and the participation of trainees in surgical procedures. We analyzed outcomes of major hepatectomies in a tertiary academic setting emphasizing the role of training and obesity on textbook outcomes (TO). - Materials and methods - 971 adult patients who underwent open major hepatectomy (Mesohepatectomy [n = 111], hemihepatectomy [n = 610], and extended hepatectomy [n = 250]) were evaluated. A TO was defined as: a negative resection margin, no grade B/C bile leak, no major complications, no in-hospital mortality, and no 30-day readmission. TOs were compared following operations performed by senior surgeons and those performed by junior surgeons under the supervision of senior surgeons and between patients with and without obesity. - Results - TO was achieved in 70.1% of patients overall (78.4% in mesohepatectomy, 73.1% in hemihepatectomy, and 59.2% in extended hepatectomy). The rate of TO was similar following operations performed by and supervised by a senior surgeon (69.3% vs 71.0%, p = 0.570). The rate of TO was significantly lower in patients with obesity (41.5% vs 74.6%, p < 0.001). Factors including increased age (odds ratio [OR] for 10-year increase = 0.83, 95% confidence interval [CI]: 0.73-0.96, p = 0.009), obesity (OR = 0.25, 95%CI: 0.16-0.37, p < 0.001), biliodigestive anastomosis (OR = 0.27, 95%CI: 0.19-0.40, p < 0.001), and portal vein resection (OR = 0.49, 95%CI: 0.28-0.87, p = 0.014) lower the rate of TO. - Conclusion - Promising outcomes are possible after major hepatectomy in an academic setting. Obese patients and those undergoing more complex surgeries had a higher risk of poor postoperative outcomes.
Online verfügbar: 15. September 2023, Artikelversion: 20. September 2023
Gesehen am 18.12.2023